Janus particles stabilized asymmetric porous composites for thermal rectification - Chao Jiang; Xiao Yang; Xingmei He; Chunyang Wang; Haisheng Chen; Xinghua Zheng; Fuxin Liang (Nature Communications)
Abstract Thermal rectification is a noteworthy phenomenon of asymmetric material, which enables the directional transfer of thermal energy. But the design and construction of such asymmetric thermal conductive materials with complex structures are full of challenges. Here, an additive manufacturing method is proposed to fabricate asymmetric porous composites from layer-by-layer cast emulsions, stabilized with Janus particles (JPs), for thermal rectification. The emulsions are remarkably stable, allowing each layer to be manipulated independently without interference, resulting in a porous structure with significant asymmetry. The thermal rectification of JPs-stabilized asymmetric porous composites (JAPCs) is investigated through both experiments and simulations. It is found that their thermal rectification ratios can be adjusted by altering the contrast between the two layers of the asymmetric porous composites, with a maximum value of 38%. This emulsion casting additive manufacturing method is suitable for large-scale production. A simple model demonstrates the potential of JAPCs to regulate thermal energy in ambient conditions with fluctuating temperatures. It is explored to achieve multilayer alternating porous composites, which cannot be achieved with gradient asymmetric approaches. This method provides a practical way to design and fabricate complicated porous structures with potential applications in additive manufacturing.